Secondary battery, method for manufacturing the same, and battery module, battery pack, and device containing the same
Patent Information
- Application Number
- CN202611115580.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-15
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]然而,与传统的燃油车能快速及时的加油相比,电动汽车一般是以较小的倍率充电,这常常需要较长的充电时间,因此给消费者造成了续航里程的焦虑,限制了电动汽车的快速普及
[0047]本申请的电池模块、电池包和装置包括本申请提供的二次电池,因而至少具有与所述二次电池相同的优势。
Smart Images

Figure CN123017882A_ABST
Abstract
Description
[0001] This application is a divisional application of patent application 202080083164.9, filed on October 15, 2020, entitled "Secondary Battery, Method for Preparing the Same, and Battery Module, Battery Pack and Device Containing the Secondary Battery". Technical Field
[0002] This application belongs to the field of secondary battery technology, specifically relating to a secondary battery and its preparation method, as well as a battery module, battery pack and device containing the secondary battery. Background Technology
[0003] Secondary batteries rely on the repeated insertion and extraction of active ions between the positive and negative electrodes for charging and discharging. They possess outstanding characteristics such as high energy density, long cycle life, and no pollution or memory effect. Therefore, as a clean energy source, secondary batteries have gradually expanded from electronic products to large-scale devices such as electric vehicles, in line with sustainable development strategies for the environment and energy.
[0004] However, unlike traditional gasoline vehicles which can be refueled quickly and readily, electric vehicles typically charge at a lower rate, often requiring longer charging times. This causes range anxiety for consumers and limits the rapid adoption of electric vehicles. Therefore, to improve the market competitiveness of electric vehicles, it is necessary to provide a secondary battery with good fast-charging performance. Summary of the Invention
[0005] The purpose of this application is to provide a secondary battery, its preparation method, and a battery module, battery pack, and device containing the secondary battery, aiming to enable the battery to have both high energy density and good fast charging performance and cycle performance.
[0006] To achieve the aforementioned objectives, this application provides a first aspect of a secondary battery, comprising a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative electrode film layer, the negative electrode film layer including a first negative electrode film layer and a second negative electrode film layer, the second negative electrode film layer being located between the negative current collector and the first negative electrode film layer; the first negative electrode film layer including a first negative electrode active material; the first negative electrode active material including a first graphite, the first graphite being artificial graphite, and the volumetric particle size distribution D of the first negative electrode active material being... v 99≤23 μm.
[0007] The secondary battery of this application employs a negative electrode sheet with a multi-layer film structure, wherein the upper first negative electrode film layer contains a first negative electrode active material, and the first negative electrode active material includes a first graphite, wherein the first graphite is artificial graphite, and the D of the first negative electrode active material is... vWith a thickness of 99≤23 μm, the negative electrode can also have a good electrochemical reaction interface and a high active ion solid-phase diffusion rate even in the high SOC (State of Charge) state of the battery, enabling the battery to be charged at a high rate in the high SOC state, thereby significantly improving the fast charging capability.
[0008] In any embodiment of this application, the first negative electrode active material satisfies 17μm ≤ D v 99 ≤ 23 μm; optional, 18 μm ≤ D v 99 ≤ 21 μm. The D of the first negative electrode active material. v Within an appropriate range, 99 can enable secondary batteries to have high energy density while also taking into account the improved fast charging capability and cycle performance due to the reduction of solid-phase conduction impedance.
[0009] In any embodiment of this application, the first negative electrode active material satisfies 8μm ≤ D v 50 ≤ 13 μm; optional, 9 μm ≤ D v 50 ≤ 12 μm. The D of the first negative electrode active material. v Within an appropriate range, 50 shortens the migration and diffusion path of active ions, which can further improve the battery's fast charging capability and cycle performance.
[0010] In any embodiment of this application, the particle size uniformity of the first negative electrode active material is 0.28 to 0.4, and optionally 0.30 to 0.36. When the particle size uniformity of the first negative electrode active material is within the above range, the active particles are rationally matched, improving processing performance, further enhancing the battery's fast charging capability and cycle performance, and also increasing the battery's energy density.
[0011] In any embodiment of this application, the first graphite includes secondary particles. Optionally, the proportion of secondary particles in the first graphite is ≥50%. Optionally, the proportion of secondary particles in the first graphite is 80% to 100%. When the first negative electrode active material contains a large number of secondary particles, the isotropy of the active particles is improved, the path of active ion insertion is shortened, and the fast charging capability of the battery can be further improved, while also improving cycle performance.
[0012] In any embodiment of this application, the particle size specific surface area of the first negative electrode active material is 0.45 m². 2 / g ~0.65m 2 / g, with an optional 0.5 m 2 / g ~ 0.63 m 2 / g. When the particle size and specific surface area of the first negative electrode active material are within an appropriate range, the fast charging performance, cycle performance, and storage performance of the battery can be further improved.
[0013] In any embodiment of this application, the first negative electrode active material satisfies: 0.6 ≤ (D v 90-D v 10) / D v 50 ≤ 1.8; optional, 0.8 ≤ (D v 90-D v 10) / D v 50 ≤ 1.4. The first negative electrode active material (D) v 90-D v 10) / D v A suitable concentration of 50 facilitates the formation of a smooth pore structure distribution in the film layer, which is beneficial for the rapid transport of active ions and reduces the liquid phase conduction impedance. Therefore, it can further improve the battery's fast charging capability and cycle performance.
[0014] In any embodiment of this application, the volume particle size distribution D of the first negative electrode active material v The diameter of the first negative electrode active material is 5 μm to 9 μm, with an optional diameter of 6 μm to 8 μm. v 10. Within an appropriate range, it can reduce the irreversible consumption of active ions and increase the mass of active material per unit volume, which is beneficial to improving the energy density, cycle performance and high-temperature storage performance of the battery.
[0015] In any embodiment of this application, the volume particle size distribution D of the first negative electrode active material v 90 has a diameter of 14μm to 21μm, with an optional diameter of 16μm to 18μm. The D of the first negative electrode active material... v Within an appropriate range, 90% can further improve the battery's fast charging capability and cycle performance.
[0016] In any embodiment of this application, the powder OI value of the first negative electrode active material is 2.0 to 4.0, optionally 2.3 to 3.6. When the powder OI value of the first negative electrode active material is within an appropriate range, it enables the battery to have more channels for rapid insertion of active ions, thereby further improving the battery's fast charging capability. Furthermore, when the powder OI value of the negative electrode active material is within an appropriate range, it can also reduce the expansion effect of the negative electrode sheet during charging, further improving the battery's cycle performance.
[0017] In any embodiment of this application, the tap density of the first negative electrode active material is 0.85 g / cm³. 3 ~ 1.4 g / cm 3 Optionally, it can be 0.9 g / cm³.3 ~ 1.2 g / cm 3 The tap density of the first negative electrode active material is within the given range, which is conducive to maintaining good contact between particles and can obtain a better interparticle void structure, ensuring smooth active ion transport channels, and enabling the battery to obtain high fast charging capability and energy density.
[0018] In any embodiment of this application, the powder compaction density of the first negative electrode active material under a pressure of 2 kN is 1.55 g / cm³. 3 ~ 1.70 g / cm 3 Optionally, it can be 1.58 g / cm³. 3 ~ 1.68 g / cm 3 The compaction density of the first negative electrode active material at a pressure of 2kN is within the given range, which enables the negative electrode film to have a high compaction density, thereby improving the energy density of the battery.
[0019] In any embodiment of this application, the specific surface area (SSA) of the first negative electrode active material is 0.8 m². 2 / g ~1.3 m 2 / g, with an optional 0.9 m 2 / g ~ 1.2 m 2 / g. The specific surface area (SSA) of the first negative electrode active material is within an appropriate range, which improves the wetting of the electrolyte and the liquid-phase transport of active ions, and is beneficial for the battery to obtain higher fast charging capability and cycle performance.
[0020] In any embodiment of this application, the specific capacity of the first negative electrode active material is 345 mAh / g to 360 mAh / g, optionally 350 mAh / g to 358 mAh / g. When the specific capacity of the first negative electrode active material is within the above range, the energy density and fast charging capability of the battery can be improved.
[0021] In any embodiment of this application, at least a portion of the surface of the first graphite has an amorphous carbon coating layer. The carbon layer formed on the surface of the first graphite can enrich active ions, reducing charge transfer resistance. Using this first graphite can further improve the battery's cycle performance and fast charging capability.
[0022] In any embodiment of this application, the first graphite accounts for ≥80% of the mass of the first negative electrode active material. Optionally, the first graphite accounts for 90% to 100% of the mass of the first negative electrode active material. The presence of more first graphite in the first negative electrode film layer can more effectively improve the fast charging capability of the battery.
[0023] In any embodiment of this application, the second negative electrode film layer includes a second negative electrode active material, which includes a second graphite, and the second graphite includes one or more of artificial graphite and natural graphite.
[0024] In any embodiment of this application, the mass percentage of artificial graphite in the second graphite is ≥50%. Optionally, the mass percentage of artificial graphite in the second graphite is 60% to 100%. The second negative electrode active material contains a large amount of artificial graphite, which can improve the energy density of the battery and improve the cycle performance and high-temperature storage performance of the battery.
[0025] In any embodiment of this application, the volume particle size distribution D of the second negative electrode active material v 99 is greater than the volumetric particle size distribution D of the first negative electrode active material. v 99. Optionally, the volumetric particle size distribution D of the second negative electrode active material. v 99 and the volume particle size distribution D of the first negative electrode active material v The 99 ratio is 2.0 to 2.6, and more preferably 2.1 to 2.4. When the second negative electrode active material and the first negative electrode active material meet the above conditions, the battery's energy density, cycle performance, and storage performance are improved, while also enabling the battery to have a high fast-charging capability.
[0026] In any embodiment of this application, the volume average particle size D of the second negative electrode active material v The thickness of 50 is 15μm to 21μm, with an optional thickness of 16.5μm to 20μm. The D of the second negative electrode active material... v Within the aforementioned range, the diffusion path of active ions is shortened, while the second negative electrode active material has a higher specific capacity, enabling the battery to have higher fast charging capability, energy density, and cycle performance.
[0027] In any embodiment of this application, the second graphite includes primary particles. Optionally, the proportion of primary particles in the second graphite is ≥50%; alternatively, the proportion of primary particles in the second graphite is 60% to 100%. The second graphite meeting the above conditions results in high anisotropy of the material, ensuring the structural stability of the graphite and increasing the compaction density of the negative electrode film, thereby improving the energy density, high-temperature storage performance, and cycle performance of the battery.
[0028] In any embodiment of this application, the particle size uniformity of the second negative electrode active material is 0.3 to 0.55, optionally 0.4 to 0.5. A particle size uniformity within the above range can further improve the cycle performance and energy density of the battery.
[0029] In any embodiment of this application, the particle size specific surface area of the second negative electrode active material is 0.35 m². 2 / g ~0.55m 2 / g, with an optional value of 0.38 m 2 / g ~ 0.50 m 2 / g. When the particle size and specific surface area of the second negative electrode active material are within an appropriate range, the irreversible consumption of active ions is reduced, which can further improve the cycle performance and storage performance of the battery.
[0030] In any embodiment of this application, the second negative electrode active material satisfies: 0.9 ≤ (D v 90-D v 10) / D v 50 ≤ 1.6; optional, 1.0 ≤ (D v 90-D v 10) / D v 50 ≤ 1.4. The second negative electrode active material (D) v 90-D v 10) / D v Within the above range, maintaining a reasonable pore structure between particles can improve the battery's fast charging performance and volumetric energy density.
[0031] In any embodiment of this application, the volume particle size distribution D of the second negative electrode active material v The thickness of the 10 is 5 μm to 14 μm, with an optional thickness of 7 μm to 12 μm. The D of the second negative electrode active material... v 10. Within the above range, the cycle performance and storage performance of the battery can be improved.
[0032] In any embodiment of this application, the volume particle size distribution D of the second negative electrode active material v 90 has a diameter of 24μm to 38μm, with an optional diameter of 26μm to 33μm. The D of the second negative electrode active material... v Within the above range, 90% can improve the battery's cycle performance and fast charging capability, and can further increase the battery's energy density.
[0033] In any embodiment of this application, the OI value of the second negative electrode active material powder is ≤14, and optionally 6 to 11. An OI value within the above range helps to shorten the insertion path of active ions, reduce battery expansion during charging, and enable the battery to have higher fast charging capability, cycle performance, and energy density.
[0034] In any embodiment of this application, the tap density of the second negative electrode active material is 0.8 g / cm³. 3 ~ 1.2 g / cm3 Optionally, it can be 0.9 g / cm³. 3 ~ 1.1 g / cm 3 The tap density of the second negative electrode active material is within the given range, which allows the active particles to maintain an excellent pore structure, thereby improving the battery's fast charging capability and energy density.
[0035] In any embodiment of this application, the powder compaction density of the second negative electrode active material under a pressure of 2 kN is 1.70 g / cm³. 3 ~ 1.85 g / cm 3 Optionally, it can be 1.75 g / cm³. 3 ~ 1.82 g / cm 3 The compaction density of the second negative electrode active material under 2kN pressure is within an appropriate range, which improves the compaction density of the negative electrode film and can enhance the energy density of the battery.
[0036] In any embodiment of this application, the specific surface area (SSA) of the second negative electrode active material is 1.0 m². 2 / g ~2.0 m 2 / g, with an optional 1.3 m 2 / g ~ 1.8 m 2 / g. A specific surface area (SSA) of the second negative electrode active material within an appropriate range is beneficial for the battery to achieve higher storage performance and cycle performance.
[0037] In any embodiment of this application, the specific capacity of the second negative electrode active material is 353 mAh / g to 370 mAh / g, optionally 359 mAh / g to 367 mAh / g. When the specific capacity of the second negative electrode active material is within the above range, the energy density of the battery can be improved, and the cycle performance of the battery can also be improved.
[0038] In any embodiment of this application, the areal density of the negative electrode film is 0.117 mg / mm². 2 ~ 0.130 mg / mm 2 The optional value is 0.120 mg / mm. 2 ~ 0.127 mg / mm 2 When the areal density of the negative electrode film is within the above-mentioned range, the energy density and fast charging capability of the battery can be further improved.
[0039] In any embodiment of this application, the compaction density of the negative electrode film is 1.65 g / cm³. 3 ~ 1.75 g / cm 3 The optional value is 1.66 g / cm³. 3 ~ 1.70 g / cm 3Within a given range, the compaction density of the negative electrode film can further improve the battery's energy density, fast charging capability, and cycle performance.
[0040] In any embodiment of this application, the thickness ratio of the second negative electrode film layer to the first negative electrode film layer is 0.7:1 to 2.3:1, optionally 0.7:1 to 1.0:1, and even more optionally 1.1:1 to 2.3:1. Keeping the thickness ratio of the second negative electrode film layer to the first negative electrode film layer within an appropriate range can further improve the battery's fast charging capability or energy density.
[0041] In any embodiment of this application, the first negative electrode active material or the second negative electrode active material further includes one or more of silicon-based materials, tin-based materials, soft carbon, hard carbon, and lithium titanate.
[0042] In any embodiment of this application, the secondary battery includes a positive electrode sheet, which includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector and including a positive electrode active material. The positive electrode active material includes one or more of lithium transition metal oxides, lithium phosphates with an olivine structure, and their respective modified compounds. Optionally, the positive electrode active material includes one or more of the lithium transition metal oxides shown in Formula 1 and their modified compounds. Li a Ni b Co c M d O e A f Formula 1, In Formula 1, 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from one or more of N, F, S and Cl.
[0043] A second aspect of this application provides a method for preparing a secondary battery, comprising at least the following steps: forming a second negative electrode film layer on at least one side of a negative electrode current collector, the second negative electrode film layer comprising a second negative electrode active material; forming a first negative electrode film layer on the surface of the second negative electrode film layer, the first negative electrode film layer comprising a first negative electrode active material; wherein the first negative electrode active material comprises a first graphite, the first graphite being artificial graphite, and the volume particle size distribution D of the first negative electrode active material is... v 99 ≤ 23 μm.
[0044] A third aspect of this application provides a battery module that includes the secondary battery of this application.
[0045] A fourth aspect of this application provides a battery pack that includes the secondary battery or battery module of this application.
[0046] The fifth aspect of this application provides an apparatus that includes at least one of the secondary battery, battery module, or battery pack of this application.
[0047] The battery module, battery pack, and device of this application include the secondary battery provided in this application, and therefore have at least the same advantages as the secondary battery. Attached Figure Description
[0048] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0049] Figure 1 This is a schematic diagram of one embodiment of the secondary battery of this application.
[0050] Figure 2 This is an exploded view of one embodiment of the secondary battery of this application.
[0051] Figure 3 This is a schematic diagram of one embodiment of the negative electrode sheet in the secondary battery of this application.
[0052] Figure 4 This is a schematic diagram of another embodiment of the negative electrode sheet in the secondary battery of this application.
[0053] Figure 5 This is a scanning electron microscope (SEM) image of one embodiment of the first negative electrode active material of this application.
[0054] Figure 6 This is a SEM image of one embodiment of the second negative electrode active material of this application.
[0055] Figure 7 This is a schematic diagram of one embodiment of the battery module of this application.
[0056] Figure 8 This is a schematic diagram of one embodiment of the battery pack of this application.
[0057] Figure 9 yes Figure 8 The exploded diagram.
[0058] Figure 10 This is a schematic diagram of one embodiment of the device for using a secondary battery as a power source according to this application. Detailed Implementation
[0059] To make the inventive objectives, technical solutions, and beneficial technical effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the embodiments described in this specification are merely illustrative and not intended to limit the scope of this application.
[0060] For simplicity, this paper only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, just as any upper limit can be combined with any other upper limit to form an undefined range. Furthermore, although not explicitly stated, every point or individual value between the endpoints of a range is included within that range. Therefore, each point or individual value can serve as its own lower or upper limit and be combined with any other point or individual value, or with other lower or upper limits, to form an undefined range.
[0061] In the description of this article, it should be noted that, unless otherwise stated, "above" and "below" include the number itself, and "several" in "one or several" means two or more.
[0062] In this description, unless otherwise stated, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0063] It should be understood that relational terms such as “first,” “second,” etc., are used only to distinguish one entity or operation from another, and do not necessarily require or imply any actual relationship or order between these entities or operations.
[0064] The foregoing description of this invention is not intended to describe every disclosed embodiment or implementation. Instead, the following description provides more specific examples of exemplary embodiments. Throughout the application, guidance is provided through a series of embodiments that can be used in various combinations. The examples listed are merely representative and should not be construed as exhaustive.
[0065] [Rechargeable Battery] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged after being discharged to activate the active materials and continue to be used.
[0066] Typically, a secondary battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During charging and discharging, active ions (such as lithium ions) repeatedly insert and extract between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through. The electrolyte, also located between the positive and negative electrodes, mainly serves to conduct ions.
[0067] [Negative electrode plate] A secondary battery includes a negative electrode sheet, which typically includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector.
[0068] The inventors discovered that the key to improving the fast-charging capability of rechargeable batteries lies in enhancing the kinetic performance of the negative electrode. Currently, most methods improve the kinetic performance of the negative electrode by thinning the negative electrode film or reducing its compaction density. However, numerous studies have shown that these methods only improve the kinetics of the battery in its low SOC state (i.e., the initial stage of charging), and have no significant effect on improving the kinetic performance in its high SOC state (i.e., the final stage of charging). This results in the rechargeable battery's fast-charging capability not being effectively improved, and may even prevent the battery from being charged at high rates. Furthermore, the battery's energy density will also be significantly reduced.
[0069] The inventors conducted further extensive research and ingeniously improved the composition of the negative electrode film, breaking through the aforementioned bottleneck. Specifically, in the secondary battery of this application, the negative electrode sheet includes a negative electrode current collector and a negative electrode film. The negative electrode film includes a first negative electrode film and a second negative electrode film, with the second negative electrode film located between the negative electrode current collector and the first negative electrode film. The first negative electrode film includes a first negative electrode active material, which includes a first graphite, which is artificial graphite, and the volume particle size distribution D of the first negative electrode active material is [not specified]. v 99≤23 μm.
[0070] The secondary battery of this application employs a negative electrode sheet with a multi-layer film structure, wherein the upper first negative electrode film layer contains a first negative electrode active material, and the first negative electrode active material includes a first graphite, wherein the first graphite is artificial graphite, and the D of the first negative electrode active material is... v With a diameter of 99 ≤ 23 μm, the negative electrode can also have a high active ion diffusion rate even in the high SOC state of the battery, thus effectively improving the fast charging capability.
[0071] Unexpectedly limited by any theory, the D of the negative electrode active material v99 has long been considered an insignificant and difficult-to-control parameter in the industry, and thus has been overlooked. However, during the research process, the inventors discovered for the first time that when the first negative electrode active material in the first negative electrode film layer includes a first graphite, which is artificial graphite, and the first negative electrode active material satisfies D... v When the particle size is ≤23 μm, the negative electrode sheet can maintain a good electrochemical reaction interface even at the end of charging (when there is a high amount of active ion intercalation, such as lithium intercalation). Furthermore, the particles of the first negative electrode active material exhibit good active ion diffusion performance, allowing active ions to quickly intercalate into the bulk phase of the first negative electrode active material and migrate rapidly. This increases the diffusion rate of active ions in the first negative electrode film during this stage. The active ions can also rapidly migrate from the first negative electrode film to the internal second negative electrode film. Therefore, the overall charging speed and depth of charge of the negative electrode sheet are significantly increased during this stage, enabling high-rate charging of the battery at high SOC and significantly improving fast charging capability. Typically, low SOC generally refers to below 30% SOC, and high SOC generally refers to above 60% SOC.
[0072] The first negative electrode active material includes a first graphite, which is artificial graphite, and the first negative electrode active material satisfies D. v 99 ≤ 23 μm can also reduce the ohmic and concentration polarization of the battery when charging at high SOC, which is beneficial to improving the cycle performance of the battery.
[0073] In some embodiments, the first negative electrode active material can satisfy D v 99 ≤ 23μm, ≤ 22.5μm, ≤ 22μm, ≤ 21.5μm, or ≤ 21μm. The D of the first negative electrode active material. v Within the aforementioned range, 99% of the lithium can be used to further improve the lithium insertion rate at high SOC and reduce polarization, thereby further improving the battery's fast charging capability and cycle performance.
[0074] In some embodiments, the D of the first negative electrode active material v 99 ≥ 15 μm, ≥ 16 μm, ≥ 17 μm, ≥ 18 μm, ≥ 19 μm, or ≥ 19.5 μm. The D of the first negative electrode active material. v Within the aforementioned range, 99% of the first negative electrode active material can achieve a higher specific capacity, thereby increasing the energy density of the battery. Furthermore, the D of the first negative electrode active material... vWithin the aforementioned range, a concentration of 99% helps reduce the number of smaller particles, allowing for the embedding of more active ions within the particles. This also facilitates the formation of unobstructed pore structures in the negative electrode film, shortening the liquid phase conduction path and thus improving the battery's fast charging capability and cycle performance. The reduced content of small particles also helps decrease side reactions of the electrolyte at the negative electrode, thereby improving the battery's high-temperature storage performance.
[0075] In some optional embodiments, the first negative electrode active material satisfies: 17 μm ≤ D v 99 ≤ 23 μm. For example, the first anode active material can satisfy 17.5 μm ≤ D v 99 ≤ 20.5 μm, 18 μm ≤ D v 99 ≤ 21 μm, 18 μm ≤ D v 99 ≤ 19 μm, 19 μm ≤ D v 99 ≤ 20.5 μm, 19.5 μm ≤ D v 99 ≤ 21μm, or 20μm ≤ D v 99 ≤ 22μm, etc. For example, D v The thickness of 99 can be 22.9μm, 22.6μm, 21.7μm, 21.1μm, 20.4μm, 19.9μm, 19.2μm, 18.1μm, or 17.6μm. Using this first negative electrode active material enables the secondary battery to simultaneously achieve high fast charging capability, cycle performance, high-temperature storage performance, and energy density.
[0076] Through in-depth research, the inventors have discovered that, in addition to meeting the above design conditions, the performance of the secondary battery can be further improved if it also meets one or more of the following parameters.
[0077] In some embodiments, the first negative electrode active material satisfies 8μm ≤ D v 50 ≤ 13 μm. Optional, the D of the first anode active material... v 50 ≤ 13 μm, ≤ 12.5 μm, or ≤ 12 μm. Optionally, the D of the first negative electrode active material... v 50 ≥ 8 μm, ≥ 9 μm, ≥ 10 μm, or ≥ 11 μm. For example, the first anode active material can satisfy 8.5 μm ≤ D v 50 ≤ 10μm, 9μm ≤ D v 50 ≤ 12 μm, 9.5 μm ≤ D v 50 ≤ 11.5 μm, 10 μm ≤ D v 50 ≤ 12 μm, 11 μm ≤ Dv 50 ≤ 12μm, 11μm ≤ D v 50 ≤ 12.5 μm, or 11.5 μm ≤ D v 50 ≤ 12.8 μm. For example, D v 50 can be 8.6μm, 9.8μm, 10.3μm, 11.2μm, 11.3μm, 11.4μm, 11.5μm, 11.7μm, 11.8μm, 12.4μm, 12.8μm, or 14.5μm.
[0078] The first negative electrode active material D v Within an appropriate range, 50 can shorten the migration path of active ions in the particles of the first negative electrode active material, while also facilitating the formation of a smooth porous structure in the first negative electrode film. This results in the negative electrode sheet possessing good liquid-phase transport performance and a good solid-phase diffusion rate of active ions, thereby further improving the battery's fast-charging capability and cycle performance. Additionally, the D of the first negative electrode active material... v Within an appropriate range, 50 can also reduce side reactions of the electrolyte on the particle surface, and improve the battery's cycle performance and high-temperature storage performance.
[0079] In some embodiments, the particle size uniformity of the first negative electrode active material is 0.28 to 0.4, for example, 0.28 to 0.38, 0.29 to 0.34, 0.30 to 0.36, or 0.31 to 0.35. When the particle size uniformity of the first negative electrode active material is within the above range, shorter liquid phase transport paths are easily formed in the first negative electrode film, while the particles have a larger contact area, which is beneficial for electron conduction and active ion transport in the negative electrode sheet, improving the battery's fast charging capability and cycle performance. Furthermore, the particles in the first negative electrode film layer can achieve close contact, thereby enabling the negative electrode sheet to achieve a higher compaction density, thus increasing the battery's energy density.
[0080] It should be noted that the particle size uniformity of the negative electrode active material can characterize the deviation of the particle size of all particles in the negative electrode active material from the volume average particle size D of the negative electrode active material. v The dispersion of 50 can reflect the uniformity of the particle size distribution of the negative electrode active material.
[0081] In some embodiments, the first negative electrode active material satisfies: 0.6 ≤ (D v 90-D v 10) / D v 50 ≤ 1.8. For example, the first negative electrode active material (D v 90-D v10) / D v 50 can be 0.8 ~ 1.4, 0.9 ~ 1.5, or 1.0 ~ 1.3. The (D) of the negative electrode active material... v 90-D v 10) / D v 50 reflects the deviation of the particle size of the larger particles and the particle size of the smaller particles in the negative electrode active material from the volume average particle size D. v The degree of 50. The first negative electrode active material (D v 90-D v 10) / D v A suitable concentration of 50 is beneficial for improving the processing performance of the first negative electrode film, enabling the first negative electrode film to have a high degree of particle distribution uniformity and unobstructed pore structure. This, in turn, helps different regions of the negative electrode film to exhibit high active ion transport performance, further improving the battery's fast charging capability and cycle performance.
[0082] In some embodiments, the volumetric particle size distribution D of the first negative electrode active material v 90 is 14μm ~ 21μm. For example, it can be 16μm ~ 18μm, 17μm ~ 19μm, or 18μm ~ 20μm. The D of the first negative electrode active material... v Within an appropriate range, 90% of the material can further increase the solid-phase diffusion rate of active ions in the negative electrode film, thereby further improving the battery's fast-charging capability and cycle performance. In addition, the negative electrode active material can also possess a high specific capacity, which helps to improve the battery's energy density.
[0083] In some embodiments, the volumetric particle size distribution D of the first negative electrode active material v The particle size is 5μm to 9μm, for example, it can be 6μm to 8μm. A lower content of small particles in the first negative electrode active material reduces side reactions between the electrolyte and the material, minimizes irreversible consumption of active ions, and improves cycle performance and high-temperature storage performance. The D of the first negative electrode active material... v 10. Within an appropriate range, the proportion of active material per unit volume can be increased, thereby improving the energy density of the battery.
[0084] In some embodiments, the particle size specific surface area of the first negative electrode active material is 0.45 m². 2 / g ~ 0.65m 2 / g, for example, can be 0.5 m 2 / g ~ 0.63 m 2 / g, 0.48 m 2 / g ~ 0.55 m 2 / g, or 0.52 m 2 / g ~ 0.6 m2 / g.
[0085] It should be noted that the "particle size specific surface area" of the negative electrode active material in this application is different from the "specific surface area" of conventional negative electrode active materials. Currently, the specific surface area (SSA) of negative electrode active materials in the industry is mostly obtained by the gas adsorption BET method, which is only used to characterize the physical adsorption specific surface area of the negative electrode active material. However, the "particle size specific surface area" of the negative electrode active material in this application is obtained by laser diffraction particle size analysis, which can be used to characterize the degree to which the morphology of the negative electrode active material deviates from sphericity.
[0086] The inventors discovered that when the specific surface area of the first negative electrode active material is within an appropriate range, it can further improve the ion insertion / extraction channels within the first negative electrode film, reduce charge exchange resistance, and create more unobstructed pores in the first negative electrode film, improving electrolyte wettability. This further enhances the solid-liquid phase transport rate of active ions in the negative electrode, thus further improving the battery's fast-charging and cycle performance. The aforementioned specific surface area of the first negative electrode active material also increases the film formation efficiency of the SEI (solid electrolyte interphase) film and reduces electrolyte consumption, further improving the battery's cycle performance. Furthermore, an appropriate specific surface area of the first negative electrode active material allows for close packing of particles within the first negative electrode film, contributing to increased battery energy density.
[0087] In some implementations, such as Figure 5 As shown, the first negative electrode active material may include secondary particles. Optionally, the proportion of secondary particles in the first negative electrode active material is ≥50%. For example, the proportion of secondary particles in the first negative electrode active material can be 55%~95%, 60%~100%, 65%~85%, 70%~100%, 75%~90%, 75%~85%, 80%~100%, 80%~90%, 85%~95%, or 90%~100%. When the first negative electrode active material contains an appropriate proportion of secondary particles, the number of active ion insertion / extraction channels in the first negative electrode film increases, and the active ion insertion path is shortened, thereby further improving the battery's fast charging capability. It also reduces polarization and decreases side reactions of the electrolyte at the negative electrode, thus enabling the battery to achieve better cycle performance and storage performance.
[0088] In some embodiments, the specific surface area (SSA) of the first negative electrode active material is 0.8 m². 2 / g ~ 1.3 m 2 / g, for example, can be 0.85 m 2 / g ~ 1.15 m2 / g, 0.9 m 2 / g ~ 1.2 m 2 / g, or 0.95 ~ 1.25 m 2 / g. When the specific surface area (SSA) of the first negative electrode active material is within an appropriate range, it can improve the wettability of the electrolyte in the film layer, enhance the liquid phase transport of active ions, and the material surface can have high electrochemical reactivity. During intercalation, active ions can be transported in the solid phase in a timely manner, while also ensuring that there are fewer side reactions between the material and the electrolyte, which is conducive to the battery obtaining higher fast charging capability and cycle performance.
[0089] In some embodiments, the OI value of the first negative electrode active material powder is 2.0 to 4.0, for example, 2.2 to 3.2, 2.3 to 3.6, 2.5 to 3.4, or 2.8 to 3.8. The low OI value of the first negative electrode active material powder, with active ion insertion ports in all directions of the particles, allows for rapid reception of active ions from the positive electrode, thereby further enhancing fast charging capability. Furthermore, the isotropic particle structure facilitates the dispersion of the expansion rate during active ion insertion, reducing cycle expansion force and thus further improving cycle performance.
[0090] In some embodiments, the tap density of the first negative electrode active material is 0.85 g / cm³. 3 ~ 1.4 g / cm 3 For example, it can be 0.9 g / cm³. 3 ~ 1.2 g / cm 3 0.95 g / cm 3 ~ 1.15 g / cm 3 1.0 g / cm 3 ~ 1.25 g / cm 3 , or 1.05 g / cm 3 ~ 1.35 g / cm 3 Within the given range, the tap density of the first negative electrode active material enables good contact between particles in the first negative electrode film layer and achieves a better interparticle void structure, ensuring unobstructed active ion transport channels and thus improving the battery's fast charging capability. Simultaneously, the close packing of particles also increases the battery's energy density.
[0091] In some embodiments, the compacted density of the first negative electrode active material at a pressure of 2 kN is 1.55 g / cm³. 3 ~ 1.70 g / cm 3 For example, it can be 1.55 g / cm³. 3 ~ 1.63 g / cm 31.58 g / cm 3 ~ 1.68 g / cm 3 or 1.60 g / cm 3 ~ 1.68 g / cm 3 The compaction density of the first negative electrode active material under a pressure of 2kN is within the given range, which enables the particles in the first negative electrode film to be in close contact, increases the content of active material per unit volume, and thus improves the energy density of the battery.
[0092] In some embodiments, the specific capacity of the first negative electrode active material is 345 mAh / g to 360 mAh / g, for example, 350 mAh / g to 358 mAh / g, 351 mAh / g to 356 mAh / g, or 352 mAh / g to 355 mAh / g. A higher specific capacity of the first negative electrode active material can improve the battery's energy density. A specific capacity within the above range also means a shorter migration path for active ions, thereby improving the battery's fast-charging capability.
[0093] In some embodiments, at least a portion of the surface of the first negative electrode active material has an amorphous carbon coating layer. Optionally, more than 80% of the surface of the first negative electrode active material is covered with an amorphous carbon coating layer. Further, 90% to 100% of the surface of the first negative electrode active material is covered with an amorphous carbon coating layer.
[0094] The amorphous carbon coating can be formed by carbonizing an organic carbon source. For example, the organic carbon source can be selected from polymer materials such as coal tar pitch, petroleum tar pitch, phenolic resin, and coconut shell.
[0095] The amorphous carbon coating layer can protect the first negative electrode active material by isolating it from the electrolyte, improving structural stability, and also increasing the diffusion rate of active ions in the particles, thereby further improving the battery's cycle performance and fast charging capability.
[0096] In some embodiments, the first graphite comprises ≥80% of the mass of the first negative electrode active material. For example, the mass percentage of the first graphite in the first negative electrode active material can be 85%~100%, 90%~100%, or 95%~100%. The presence of a large amount of first graphite in the first negative electrode film layer can fully leverage the role of the first negative electrode active material in improving the diffusion performance of active ions when the negative electrode sheet has a high level of active ion intercalation, resulting in a higher charging speed and depth of charge for the negative electrode sheet as a whole at this stage, effectively improving the battery's fast charging capability.
[0097] In some embodiments, the first negative electrode active material in the negative electrode sheet may optionally include a certain amount of other commonly used negative electrode active materials, such as natural graphite, silicon-based materials, tin-based materials, soft carbon, hard carbon, and lithium titanate.
[0098] In some embodiments, the first negative electrode active material further includes a silicon-based material. The silicon-based material may include elemental silicon, silicon oxide (SiO2), etc. x Silicon-based materials can be selected from one or more of the following: (0 < x < 2), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Silicon-based materials can improve the pore structure of the first negative electrode film, facilitating electrolyte wetting and retention, and also increasing electrode capacity, thereby further enhancing the battery's fast-charging capability and energy density.
[0099] In some embodiments, when the first negative electrode active material also includes a silicon-based material, the mass percentage of the silicon-based material in the first negative electrode active material is ≤10%. For example, the mass percentage of the silicon-based material in the first negative electrode active material can be 1% to 8%, 2% to 6%, or 3% to 7%. Including an appropriate amount of silicon-based material in the first negative electrode active material can improve the battery's fast charging capability and energy density, while also enabling the battery to further achieve higher cycle performance and high-temperature storage performance.
[0100] In the secondary battery of this application, the second negative electrode film layer includes a second negative electrode active material. The second negative electrode active material includes a second graphite. The second graphite and the first graphite may be made of the same or different materials.
[0101] In the secondary battery of this application, the second graphite can be selected from one or more of artificial graphite and natural graphite. The second negative electrode active material can have high cycle stability and high specific capacity, thereby giving the battery high cycle performance and energy density.
[0102] In some embodiments, the second graphite comprises artificial graphite. Optionally, the mass percentage of artificial graphite in the second graphite is ≥50%. For example, the mass percentage of artificial graphite in the second graphite can be 60%~100%, 70%~100%, 80%~100%, or 90%~100%. Artificial graphite has good structural stability. The presence of a significant amount of artificial graphite in the second negative electrode active material helps maintain a good pore structure in the inner layer of the negative electrode film (the second negative electrode film), resulting in high electrolyte wettability and liquid retention in the inner layer. This further enhances the overall ion transport rate of the negative electrode sheet and improves the battery's fast-charging capability. Furthermore, the presence of a significant amount of artificial graphite in the second negative electrode active material also improves its electrolyte compatibility, enhancing the battery's cycle performance and high-temperature storage performance.
[0103] In some implementations, the second graphite may include both artificial graphite and natural graphite.
[0104] In some embodiments, when the second graphite comprises both artificial and natural graphite, the mass percentage of natural graphite in the second negative electrode active material is ≤40%, for example, 5%~40%, 10%~30%, or 10%~20%. Including a certain amount of natural graphite in the second negative electrode active material can further improve the kinetic performance of the negative electrode sheet, enabling the battery to achieve a higher fast-charging capability. By appropriately proportioning artificial and natural graphite in the second negative electrode active material, the battery's fast-charging capability, cycle performance, and high-temperature storage performance can be balanced.
[0105] In some embodiments, the volumetric particle size distribution D of the second negative electrode active material v 99 is greater than the volumetric particle size distribution D of the first negative electrode active material. v 99. D of the second negative electrode active material v A higher concentration of 99 is beneficial for increasing the capacity of the negative electrode and can also reduce side reactions between the electrolyte and the negative electrode active material, thereby improving the battery's energy density, cycle performance, and high-temperature storage performance.
[0106] In some embodiments, the D of the second negative electrode active material v 99 can be 28μm ~ 55μm, 30μm ~ 50μm, 40μm ~ 55μm, 40μm ~ 50μm, or 45μm ~ 50μm. For example, the D of the second negative electrode active material... v 99 can be 41.6μm, 44.5μm, 45.2μm, 48.7μm, 50.1μm, 52.3μm, or 54.8μm.
[0107] In some embodiments, the D of the second negative electrode active material v 99 and the first negative electrode active material D v The 99 ratio is 2.0 to 2.6, for example, it can be 2.1 to 2.45, 2.1 to 2.4, 2.2 to 2.6, or 2.2 to 2.5. The D of the second negative electrode active material... v 99 and the first negative electrode active material D v A 99 ratio within the aforementioned range can improve the battery's energy density, cycle performance, and high-temperature storage performance, while also ensuring that the negative electrode has high active ion and electron transport capabilities, enabling the battery to further possess high fast charging capabilities.
[0108] In some embodiments, the volume average particle size D of the second negative electrode active material v50 represents 15μm to 21μm. For example, it could be 15μm to 18μm, 16μm to 19μm, 16μm to 18μm, 16μm to 17μm, 16.5μm to 20μm, 17μm to 20μm, or 17μm to 21μm. For example, D... v The thickness of 50 can be 15.9 μm, 16.1 μm, 16.5 μm, 16.6 μm, 16.8 μm, 16.9 μm, or 17.5 μm. The D of the second negative electrode active material... v Within the aforementioned range, the second negative electrode film layer possesses both high active ion diffusion capability and reduced side reactions of the electrolyte at the negative electrode, thereby enabling the battery to achieve high fast charging capability and cycle performance. Furthermore, this second negative electrode active material also exhibits high specific capacity, allowing the battery to achieve high energy density.
[0109] In some embodiments, the second negative electrode active material satisfies: 0.9 ≤ (D v 90-D v 10) / D v 50 ≤ 1.6. For example, the second negative electrode active material (D v 90-D v 10) / D v 50 can be 1.0 ~ 1.4, 1.05 ~ 1.35, or 1.1 ~ 1.25. The (D) of the second negative electrode active material... v 90-D v 10) / D v Within the aforementioned range, 50 can improve particle packing performance, increase the proportion of active materials, and thus improve the volumetric energy density of the battery. In particular, the overall particle distribution uniformity of the negative electrode film layer and the formation of a reasonable pore structure between particles can improve the battery's fast charging capability.
[0110] In some embodiments, the volumetric particle size distribution D of the second negative electrode active material v The particle size of 10 ranges from 5 μm to 14 μm, for example, it can be 6 μm to 10 μm, 7 μm to 12 μm, or 7 μm to 9 μm. Having fewer small particles in the second negative electrode active material reduces side reactions of the electrolyte at the negative electrode and the irreversible consumption of active ions, thereby improving the battery's cycle performance and storage performance.
[0111] In some embodiments, the volumetric particle size distribution D of the second negative electrode active material vThe particle size of the second negative electrode active material is 24μm to 38μm, for example, it can be 26μm to 33μm. Having fewer large particles in the second negative electrode active material improves the active ion and electron transport performance of the negative electrode film, reduces polarization, and enhances the battery's cycle performance and fast charging capability. Furthermore, the second negative electrode active material can also have a higher specific capacity, which can further improve the battery's energy density.
[0112] In some implementations, alternatively, such as Figure 6 As shown, the second graphite includes primary particles, and the proportion of primary particles in the second graphite is ≥50%. For example, the proportion of primary particles in the second graphite can be 55%~95%, 60%~100%, 65%~90%, 65%~80%, 70%~100%, 75%~90%, 80%~100%, 90%~100%, or 95%~100%. The inclusion of an appropriate proportion of primary particles in the second negative electrode active material can achieve higher structural stability and reduce side reactions of the electrolyte at the negative electrode, thereby improving the high-temperature storage performance and cycle performance of the battery. Furthermore, using this second negative electrode active material can also increase the compaction density of the negative electrode film, thereby increasing the energy density of the battery.
[0113] In some embodiments, the particle size uniformity of the second negative electrode active material is 0.3 to 0.55. For example, the particle size uniformity of the second negative electrode active material is 0.39 to 0.49, 0.4 to 0.5, 0.42 to 0.48, or 0.43 to 0.46. A particle size uniformity within the above range can further improve the compaction density of the negative electrode film, thereby increasing the energy density of the battery; simultaneously, the second negative electrode film can have good electrolytic wetting channels, thereby enabling the battery to have higher cycle performance.
[0114] In some embodiments, the particle size specific surface area of the second negative electrode active material is 0.35 m². 2 / g ~ 0.55m 2 / g, for example, can be 0.36 m 2 / g ~ 0.48m 2 / g, 0.38 m 2 / g ~ 0.50 m 2 / g, or 0.42 m 2 / g ~ 0.53 m 2 / g. When the particle size and specific surface area of the second negative electrode active material are within an appropriate range, the second negative electrode film layer can possess numerous ion insertion / extraction channels and a suitable pore structure, ensuring low impedance of the negative electrode. Simultaneously, it further reduces the consumption of electrolyte and active ions, thereby further improving the battery's cycle performance and storage performance. Furthermore, an appropriate particle size and specific surface area of the second negative electrode active material also allows for close packing of the particles in the second negative electrode film layer, increasing the battery's energy density.
[0115] In some embodiments, the specific surface area (SSA) of the second negative electrode active material is 1.0 m². 2 / g ~ 2.0 m 2 / g, for example, can be 1.3 m 2 / g ~ 1.8 m 2 / g. When the specific surface area (SSA) of the second negative electrode active material is within an appropriate range, the second negative electrode film can have high active ion solid-phase diffusion performance, while also ensuring that there are fewer side reactions between the material and the electrolyte, which is beneficial for the battery to obtain high fast charging capability, cycle performance and storage performance.
[0116] In some embodiments, the OI value of the second negative electrode active material powder is ≤14, preferably 5~14, 6~11, or 7~10. The second negative electrode active material not only has good active ion intercalation performance, but also enables the negative electrode film layer to have low cycle expansion, thereby giving the battery high fast charging capability, cycle performance, and energy density.
[0117] In some embodiments, the specific capacity of the second negative electrode active material is 353 mAh / g to 370 mAh / g, for example, 359 mAh / g to 367 mAh / g, or 360 mAh / g to 365 mAh / g. A higher specific capacity of the second negative electrode active material can further improve the energy density of the battery. A specific capacity within the above range also indicates better cycle stability of the material, thereby improving the cycle performance of the battery.
[0118] In some embodiments, the tap density of the second negative electrode active material is 0.8 g / cm³. 3 ~ 1.2 g / cm 3 For example, it can be 0.9 g / cm³. 3 ~ 1.1 g / cm 3 , or 0.95 g / cm 3 ~ 1.08 g / cm 3Within the given range, the tap density of the second negative electrode active material enables close contact between particles in the second negative electrode film layer, while maintaining an excellent pore structure between active particles, thereby improving the battery's fast charging capability and energy density.
[0119] In some embodiments, the powder compaction density of the second negative electrode active material at a pressure of 2 kN is 1.70 g / cm³. 3 ~ 1.85 g / cm 3 For example, it can be 1.75 g / cm³. 3 ~ 1.82 g / cm 3 The compaction density of the second negative electrode active material under 2kN pressure is within an appropriate range, which can increase the compaction density of the negative electrode film, thereby improving the battery energy density.
[0120] In the secondary battery of this application, the second negative electrode active material may optionally include a certain amount of other commonly used negative electrode active materials, in addition to the second graphite mentioned above, such as one or more of silicon-based materials, tin-based materials, soft carbon, hard carbon, and lithium titanate.
[0121] The negative electrode film layer of this application is typically formed by coating and drying a negative electrode slurry. The negative electrode slurry coating is usually formed by dispersing the negative electrode active material, along with optional conductive agents and binders, in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water.
[0122] In the secondary battery of this application, the first or second negative electrode film layer typically comprises a negative electrode active material and optional binders, optional conductive agents, and other optional additives. Those skilled in the art can make selections based on actual needs. As an example, conductive agents may include one or more of superconducting carbon, carbon black (e.g., acetylene black, Ketjen black, etc.), carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Binders may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resin, polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). Other optional additives include thickeners (such as sodium carboxymethyl cellulose CMC-Na), PTC thermistor materials, etc.
[0123] In some embodiments, the areal density of the negative electrode film is 0.117 mg / mm². 2 ~ 0.130 mg / mm 2 For example, it could be 0.117 mg / mm. 2 ~ 0.125 mg / mm 2 0.118 mg / mm 2 ~ 0.122 mg / mm 20.120 mg / mm 2 ~ 0.127mg / mm 2 or 0.121 mg / mm 2 ~ 0.125 mg / mm 2 It should be noted that the areal density of the negative electrode film refers to the overall areal density of the negative electrode film (i.e., the sum of the areal densities of the first and second negative electrode films). Having an areal density within the aforementioned range allows the negative electrode to have a higher capacity and reduces the migration distance and impedance of active ions and electrons within the film, thereby further improving the battery's energy density and fast-charging capability.
[0124] In some embodiments, the compaction density of the negative electrode film is 1.65 g / cm³. 3 ~ 1.75 g / cm 3 For example, it can be 1.65 g / cm³. 3 ~ 1.68 g / cm 3 1.66 g / cm 3 ~ 1.70 g / cm 3 , or 1.68 g / cm 3 ~ 1.72 g / cm 3 It should be noted that the compaction density of the negative electrode film refers to the overall compaction density of the negative electrode film (i.e., the ratio of the areal density to the thickness of the negative electrode film). Within the given range, a compaction density of the negative electrode film enables the negative electrode sheet to possess both high reversible capacity and good low-cycle expansion performance and kinetic performance, thereby further improving the battery's energy density, fast-charging capability, and cycle performance.
[0125] In some embodiments, the thickness ratio of the second negative electrode film to the first negative electrode film is 0.7:1 to 2.3:1. By keeping the thickness ratio of the second negative electrode film to the first negative electrode film within an appropriate range, the fast charging capability or energy density of the battery can be further improved. To obtain higher fast charging capability, the thickness ratio of the second negative electrode film to the first negative electrode film can optionally be 0.7:1 to 1.0:1, 0.75:1 to 0.9:1, or 0.8:1 to 1.0:1. To obtain higher energy density, the thickness ratio of the second negative electrode film to the first negative electrode film can optionally be 1.1:1 to 2.3:1, 1.3 to 2.1:1, or 1.5 to 2:1.
[0126] In some embodiments, the total thickness of the negative electrode film can be selected as 60 μm to 90 μm, for example, 65 μm to 80 μm. The total thickness of the negative electrode film is the sum of the thicknesses of the first negative electrode film and the second negative electrode film.
[0127] In the secondary battery of this application, the negative electrode current collector can be a metal foil or a composite current collector (a composite current collector can be formed by setting metal material on a polymer substrate). As an example, the negative electrode current collector can be copper foil.
[0128] In the secondary battery of this application, the negative electrode film layer can be disposed on one side of the negative electrode current collector, or it can be disposed on both sides of the negative electrode current collector simultaneously. For example, the negative electrode current collector has two opposite sides in its own thickness direction, and the negative electrode film layer is disposed on any one or both of the opposite sides of the negative electrode current collector.
[0129] Figure 3 The diagram shows one embodiment of the negative electrode 10 of this application. The negative electrode 10 is composed of a negative current collector 101, a second negative electrode film layer 103 disposed on both sides of the negative current collector 101, and a first negative electrode film layer 102 disposed on the second negative electrode film layer 103.
[0130] Figure 4 A schematic diagram of another embodiment of the negative electrode 10 of this application is shown. The negative electrode 10 is composed of a negative current collector 101, a second negative electrode film layer 103 disposed on one side of the negative current collector, and a first negative electrode film layer 102 disposed on the second negative electrode film layer 103.
[0131] It should be noted that the parameters of each negative electrode film layer given in this application (such as film layer thickness, compaction density, areal density, etc.) refer to the parameter range of a single side of the film layer. When the negative electrode film layer is disposed on both sides of the negative electrode current collector, the film layer parameters on either side that meet the requirements of this application are considered to fall within the protection scope of this application. Furthermore, the film layer thickness, compaction density, areal density, etc. ranges mentioned in this application refer to the film layer parameters after cold pressing and compaction and used for assembling the battery.
[0132] Furthermore, in the secondary battery of this application, the negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet of this application may also include a conductive undercoat layer (e.g., composed of a conductive agent and a binder) disposed between the negative electrode current collector and the second negative electrode film layer. In other embodiments, the negative electrode sheet of this application further includes a protective covering layer covering the surface of the first negative electrode film layer.
[0133] In this application, the D of the negative electrode active material v 99. D v 90. D v 50. D v10. Particle size uniformity and specific surface area can both be determined using laser diffraction particle size analysis. For example, refer to standard GB / T 19077.1-2016 and use a laser particle size analyzer (e.g., Malvern Master Size 3000) for determination.
[0134] Among them, D v 99 represents the particle size corresponding to a cumulative volume distribution percentage of 99% for the negative electrode active material; D v 90 represents the particle size corresponding to a cumulative volume distribution percentage of 90% for the negative electrode active material; D v 50 represents the particle size corresponding to a cumulative volume distribution percentage of 50% for the negative electrode active material; D v 10 represents the particle size corresponding to a cumulative volume distribution percentage of 10% for the negative electrode active material.
[0135] In this application, primary particles and secondary particles have the meanings known in the art. Primary particles refer to particles that have not formed aggregates. Secondary particles refer to particles that are aggregated from two or more primary particles. Primary and secondary particles can be easily distinguished by taking SEM images using a scanning electron microscope.
[0136] The proportion of primary or secondary particles in the negative electrode active material can be determined using instruments and methods known in the art, such as scanning electron microscopy. An exemplary test method for the proportion of secondary particles includes: laying and adhering the negative electrode active material onto conductive adhesive to form a sample 6 cm long × 1.1 cm wide; and testing the particle morphology using a scanning electron microscope (e.g., ZEISS Sigma 300). The test can be referenced in JY / T010-1996. To ensure the accuracy of the test results, multiple (e.g., 5) different regions can be randomly selected from the sample for scanning tests, and at a certain magnification (e.g., 1000x), the percentage of secondary particles in each region relative to the total number of particles is calculated; this is the proportion of secondary particles in that region. The average of the test results from multiple test regions is taken as the test result. To ensure the accuracy of the test results, multiple test samples (e.g., 10) can be used to repeat the above test, and the average of each test sample is taken as the final test result. Similarly, the proportion of primary particles in the second negative electrode active material can also be tested.
[0137] In this application, the OI value of the negative electrode active material powder has a meaning known in the art and can be tested using methods known in the art. For example, an X-ray powder diffractometer (e.g., Bruker D8 Discover) can be used to obtain the X-ray diffraction pattern of the negative electrode active material according to JIS K0131-1996 and JB / T4220-2011; then, according to OI value = C 004 / C 110 The OI value of the negative electrode active material powder was calculated. Among them, C 004 C represents the peak area of the characteristic diffraction peak of the graphite 004 crystal plane. 110 The peak area is the characteristic diffraction peak of the graphite 110 crystal plane.
[0138] In the X-ray diffraction analysis test of this application, a copper target can be used as the anode target, CuKα rays can be used as the radiation source, the ray wavelength λ=1.5418Å, the scanning 2θ angle range is 20° ~ 80°, and the scanning rate can be 4° / min.
[0139] In this application, the tap density of the negative electrode active material has a meaning known in the art and can be tested using methods known in the art. For example, it can be determined using a powder tap density tester according to standard GB / T 5162-2006. If Dandong Baite BT-301 is used, the test parameters are as follows: vibration frequency: 250±15 times / minute, amplitude: 3±0.2mm, number of vibrations: 5000 times, measuring cylinder: 25 mL.
[0140] In this application, the compacted density of the negative electrode active material under 2kN pressure has a meaning known in the art and can be determined by methods known in the art. For example, it can be determined by an electronic pressure testing machine (e.g., UTM7305) according to standard GB / T24533-2009. An exemplary test method is as follows: Weigh 1g of negative electrode active material and add it to a container with a bottom area of 1.327cm². 2 In the mold, the pressure is increased to 200 kg (equivalent to 2 kN), held for 30 seconds, then depressurized and held for 10 seconds. The compaction density of the negative electrode active material under 2 kN pressure is then recorded and calculated.
[0141] In this application, the specific surface area (SSA) of the negative electrode active material has a meaning known in the art and can be determined by methods known in the art. For example, referring to GB / T 19587-2017, the nitrogen adsorption specific surface area analysis method is used for testing, and the result is calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, Inc., USA.
[0142] The specific capacity of the negative electrode active material has a meaning known in the art and can be tested using methods known in the art. An exemplary test method is as follows: The prepared negative electrode active material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed uniformly with solvent N-methylpyrrolidone (NMP) at a mass ratio of 91.6:1.8:6.6 to form a slurry; the prepared slurry is coated onto a copper foil current collector and dried in an oven for later use. A lithium metal sheet is used as the counter electrode, and a polyethylene (PE) film is used as the separator. Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain the electrolyte, wherein the concentration of LiPF6 is 1 mol / L. A CR2430 coin cell is assembled in an argon-protected glove box. After the obtained coin cells were left to stand for 12 hours, they were discharged at 25°C with a constant current of 0.05C to 0.005V. After standing for 10 minutes, they were discharged again with a constant current of 50 μA to 0.005V, and then discharged again with a constant current of 10 μA to 0.005V. Finally, they were charged at a constant current of 0.1C to 2V, and the charging capacity was recorded. The ratio of the charging capacity to the mass of the negative electrode active material is the specific capacity of the prepared negative electrode active material.
[0143] In this application, the thickness of the negative electrode film layer has a meaning known in the art and can be tested using methods known in the art, such as a micrometer (e.g., Mitutoyo 293-100 model, with an accuracy of 0.1 μm).
[0144] In this application, the thicknesses of the first and second negative electrode films can be measured using a scanning electron microscope (e.g., ZEISS Sigma 300). Sample preparation is as follows: First, the negative electrode sheet is cut into a sample of a certain size (e.g., 2cm × 2cm), and fixed to the sample stage with paraffin wax. Then, the sample stage is installed in the sample holder and locked in place. The argon ion cross-section polisher (e.g., IB-19500CP) is powered on and a vacuum is applied (e.g., 10...). -4 Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours), and adjust the sample stage to swing mode to begin polishing. Sample testing can refer to JY / T010-1996. To ensure the accuracy of the test results, multiple (e.g., 5) different regions can be randomly selected from the sample to be tested for scanning. At a certain magnification (e.g., 500x), the thicknesses of the first and second negative electrode films in the scale test areas are read, and the average value of multiple test areas is taken as the test result.
[0145] In this application, the areal density of the negative electrode film has a meaning known in the art and can be tested using methods known in the art. For example, take a negative electrode sheet that has been coated on one side and cold-pressed (if it is a negative electrode sheet coated on both sides, the negative electrode film layer on one side can be wiped off first), cut it into a small circular piece with an area of S1, weigh it, and record its weight as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the negative current collector, and record it as M0. The areal density of the negative electrode film layer = (weight of the negative electrode sheet M1 - weight of the negative current collector M0) / S1.
[0146] In this application, the compaction density of the negative electrode film has a meaning known in the art and can be tested using methods known in the art. The compaction density of the negative electrode film = areal density of the negative electrode film / thickness of the negative electrode film.
[0147] It should be noted that the above-mentioned tests on various parameters of the negative electrode film or negative electrode active material can be conducted by sampling during the battery manufacturing process or by sampling from the prepared secondary battery.
[0148] When the test samples are taken from the prepared secondary batteries, as an example, the sampling can be performed according to the following steps: (1) Discharge the secondary battery (for safety reasons, the battery is generally left fully discharged); after removing the battery, take out the negative electrode plate and soak it in dimethyl carbonate (DMC) for a certain period of time (e.g., 2 to 10 hours); then take out the negative electrode plate and dry it at a certain temperature and time (e.g., 60°C, 4 hours), and then take out the negative electrode plate. At this time, samples can be taken from the dried negative electrode plate to test the parameters related to the negative electrode film layer mentioned above in this application.
[0149] (2) Bake the negative electrode sheet after drying in step (1) at a certain temperature and time (e.g., 400℃, 2h). Select any area in the baked negative electrode sheet and first take a sample of the first negative electrode active material (you can use a blade to scrape the powder for sampling). The scraping depth should not exceed the boundary between the first negative electrode film layer and the second negative electrode film layer. Then take a sample of the second negative electrode active material in the same way.
[0150] Because during the preparation of the negative electrode film, there may be an interfusion layer in the boundary region between the first negative electrode film and the second negative electrode film (i.e., the first negative electrode active material and the second negative electrode active material exist in the interfusion layer at the same time), in order to ensure the accuracy of the test, when sampling the second negative electrode active material, the interfusion layer can be scraped off first, and then the powder of the second negative electrode active material can be scraped off and sampled.
[0151] (3) The first negative electrode active material and the second negative electrode active material collected in step (2) are respectively screened (e.g., screened through a 200-mesh sieve) to finally obtain the first negative electrode active material and the second negative electrode active material samples that can be used to test the material parameters of the present application.
[0152] During the above sampling process, an optical microscope or a scanning electron microscope can be used to help determine the location of the boundary between the first negative electrode film layer and the second negative electrode film layer.
[0153] [Positive electrode plate] In the secondary battery of this application, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector and comprising a positive electrode active material. For example, the positive current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0154] In the secondary battery of this application, the positive electrode active material may be any positive electrode active material known in the art for use in secondary batteries. For example, the positive electrode active material may include one or more of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and their modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and their respective modified compounds. This application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for secondary batteries may also be used.
[0155] In some alternative embodiments, to further improve the energy density of the battery, the positive electrode active material may include one or more of the lithium transition metal oxides and their modified compounds shown in Formula 1. Li a Ni b Co c M d O e A f Formula 1, In Formula 1, 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from one or more of N, F, S and Cl.
[0156] In this application, the modified compounds of the above-mentioned materials can be used to dope or surface-coat the positive electrode active material.
[0157] In the secondary battery of this application, the positive electrode film layer typically comprises a positive electrode active material, an optional binder, and an optional conductive agent. It is usually formed by coating a positive electrode slurry and then drying and cold pressing it. The positive electrode slurry is typically formed by dispersing the positive electrode active material, optional conductive agent, and binder in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP).
[0158] As an example, the binder used for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0159] As an example, the conductive agent used for the positive electrode film may include one or more of superconducting carbon, carbon black (e.g., acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0160] In the secondary battery of this application, the positive electrode current collector can be a metal foil or a composite current collector (a composite current collector can be formed by depositing metal material on a polymer substrate). As an example, the positive electrode current collector can be aluminum foil.
[0161] [Electrolytes] The secondary battery of this application does not have specific restrictions on the type of electrolyte, and can be selected according to needs. For example, the electrolyte can be selected from at least one of solid electrolytes and liquid electrolytes (i.e., electrolyte solutions).
[0162] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0163] In some embodiments, the electrolyte salt may be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorodioxalate phosphate), and LiTFOP (lithium tetrafluorooxalate phosphate).
[0164] In some embodiments, the solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0165] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, additives that improve battery low-temperature performance, etc.
[0166] [Isolation membrane] Secondary batteries using electrolytes, and some secondary batteries using solid electrolytes, also include a separator. The separator is positioned between the positive and negative electrodes, serving a separating function. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected. In some embodiments, the separator material can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.
[0167] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0168] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the aforementioned electrode assembly and electrolyte.
[0169] In some implementations, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, aluminum shell, or steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0170] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. Figure 1 This is an example of a square-structured secondary battery 5.
[0171] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. Positive electrode sheets, negative electrode sheets, and a separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The secondary battery 5 may contain one or more electrode assemblies 52, which can be adjusted according to requirements.
[0172] In some implementations, the secondary batteries can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module.
[0173] Figure 7 This is battery module 4, used as an example. (See reference...) Figure 7 In battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.
[0174] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.
[0175] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0176] Figure 8 and Figure 9 This is battery pack 1 as an example. (See reference...) Figure 8 and Figure 9 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0177] Preparation method The second aspect of this application provides a method for preparing a secondary battery, comprising the following steps: forming a second negative electrode layer on at least one side of a negative electrode current collector, the second negative electrode layer comprising a second negative electrode active material; forming a first negative electrode layer on the surface of the second negative electrode layer, the first negative electrode layer comprising a first negative electrode active material; wherein the first negative electrode active material comprises a first graphite, the first graphite being artificial graphite, and the volume particle size distribution D of the first negative electrode active material is... v 99≤23μm.
[0178] In the preparation method of the secondary battery of this application, a first negative electrode active material, along with optional conductive agents, optional binders, and other optional additives, can be dispersed in a solvent (e.g., deionized water) to form a first negative electrode active material slurry. A second negative electrode active material, along with optional conductive agents, optional binders, and other optional additives, can be dispersed in a solvent (e.g., deionized water) to form a second negative electrode active material slurry.
[0179] In the preparation method of the secondary battery of this application, the first negative electrode active material slurry and the second negative electrode active material slurry can be coated simultaneously at one time or coated in two separate times.
[0180] In some embodiments, the first negative electrode active material slurry and the second negative electrode active material slurry are coated simultaneously in one step. Simultaneous coating in one step can improve the adhesion between the first and second negative electrode film layers, which helps to reduce the interfacial resistance of the film layers and further improves the battery's fast charging capability and cycle performance.
[0181] The second negative electrode active material used in this application is obtained commercially or prepared by methods known in the art. Those skilled in the art can make an appropriate selection based on the actual application environment.
[0182] In the first negative electrode active material used in this application, the first graphite can be prepared using a method developed by the inventors. Specifically, the preparation method of the first graphite includes the following steps a) to e).
[0183] a) Providing petroleum coke feedstock, wherein the petroleum coke feedstock has a D v 99 is 15 μm ~ 21 μm. Optional, the D of the petroleum coke feedstock... v 99 is 16 μm ~ 21 μm, 17 μm ~ 21 μm, 17 μm ~ 20 μm, or 17 μm ~ 19 μm.
[0184] b) The petroleum coke feedstock is shaped and graded to obtain a precursor, wherein the precursor D v 99 has a diameter of 16μm to 22μm. Optional, the precursor's D...v 99 refers to 17μm ~ 22μm, 17.5μm ~ 20μm, 18μm ~ 21μm, or 18μm ~ 20μm.
[0185] c) Granulating the precursor to obtain a granulated product, wherein the granulated product has a D v 99 has a particle size of 17 μm to 24 μm. Optional, granulation product D... v 99 is 18 μm ~ 24 μm, 19 μm ~ 22 μm, or 19 μm ~ 21 μm.
[0186] d) The granulated product is graphitized at a temperature of 2800℃ ~ 3200℃, and then sieved to obtain artificial graphite, wherein the D of the artificial graphite is... v 99 has a thickness of 17 μm to 26 μm. Optional, the D of artificial graphite... v 99 is 18 μm ~ 24 μm, 19 μm ~ 26 μm, 21 μm ~ 26 μm, 20 μm ~ 25 μm, 20 μm ~ 23 μm, or 19.5 μm ~ 22 μm.
[0187] e) The artificial graphite is coated with an organic carbon source, followed by heat treatment to form an amorphous carbon coating layer on at least a portion of the surface of the artificial graphite. After sieving, a first graphite is obtained. The first graphite has a D... v 99≤23 μm.
[0188] In some embodiments, the petroleum coke feedstock in step a) may include one or more of petroleum-based non-needle coke and petroleum-based needle coke. For example, the petroleum coke feedstock may be selected from one or more of calcined petroleum coke, needle-shaped green petroleum coke, and non-needle-shaped green petroleum coke. For instance, the petroleum coke feedstock may include non-needle-shaped green petroleum coke.
[0189] In some embodiments, the D of the petroleum coke feedstock in step a) v 50 is 5.5μm ~ 11μm; for example, 6μm ~ 11μm, 7μm ~ 10μm, 6.5μm ~ 8μm, 7μm ~ 8.5μm, or 8μm ~ 11μm. This affects the D of the petroleum coke feedstock. v 50 is within an appropriate range, which facilitates the control of the D of the first graphite. v 50 is within the required range.
[0190] In some embodiments, the volatile matter content C1 of the petroleum coke feedstock in step a) can be 1% to 12%; for example, 3% to 10%, 5% to 9%, 6% to 8%, 7% to 8.5%, or 7.5% to 8.5%, etc. This can improve the particle size distribution of the first graphite. The volatile matter content of the petroleum coke feedstock can be tested using methods known in the art. For example, it can be determined according to SH / T 0026-1990.
[0191] In some implementations, the precursor D in step b) v 50 is 7μm ~ 12μm; for example, 7.5 μm ~ 11μm, or 8 μm ~ 10 μm.
[0192] In some implementations, the particle size uniformity U1 of the precursor in step b) satisfies 0.2 ≤ U1 ≤ 0.55; for example, 0.2 ≤ U1 ≤ 0.5, 0.25 ≤ U1 ≤ 0.45, 0.3 ≤ U1 ≤ 0.45, 0.3 ≤ U1 ≤ 0.4, 0.35 ≤ U1 ≤ 0.55, or 0.35 ≤ U1 ≤ 0.45. This can improve the particle size uniformity of the first graphite.
[0193] In some embodiments, the D of the granulated product in step c) v 50 is 8 μm ~ 14 μm; for example, 10 μm ~ 14 μm, or 11 μm ~ 13 μm.
[0194] In some embodiments, in step c), the precursor and binder can be mixed; then high-temperature granulation is performed. The binder can be asphalt. In step c), granulation can be performed using equipment known in the art, such as a granulator. Optionally, the mixing temperature can be controlled at 20°C to 40°C, the mixing frequency at 35 Hz to 38 Hz, and the mixing time at 50 min to 65 min; then the temperature can be increased to 300°C to 400°C at a rate of 6 to 10°C / min and held for 1 h to 2 h; then the temperature can be increased to 500°C to 600°C at a rate of 6 to 10°C / min and held for 1 h to 2 h; then the temperature can be increased to 700°C to 800°C at a rate of 6 to 10°C / min and held for 1 h to 2 h; then the temperature can be allowed to cool naturally to obtain the granulated product.
[0195] In some embodiments, in step c), the amount of binder C2 added during the granulation process satisfies the condition that 8% ≤ C1 + C2 ≤ 17% relative to the volatile matter content C1 of the petroleum coke feedstock. This improves the degree of granulation, ensuring that the proportion of secondary particles in the first graphite meets the requirements. For example, 8% ≤ C1 + C2 ≤ 15%, 9% ≤ C1 + C2 ≤ 14%, or 10% ≤ C1 + C2 ≤ 13%. The amount of binder C2 added during the granulation process is the percentage of the weight of the binder added during the granulation process relative to the total weight of the precursor.
[0196] In some embodiments, in step c), the amount of binder C2 added during the granulation process satisfies the following relationship: 21% ≤ (C1+C2) / U1 × 100% ≤ 50% relative to the volatile matter content C1 of the petroleum coke feedstock and the particle size consistency U1 of the precursor. This can further improve the degree of granulation. For example, 25% ≤ (C1+C2) / U1 × 100% ≤ 45%, 25% ≤ (C1+C2) / U1 × 100% ≤ 38%, 27% ≤ (C1+C2) / U1 × 100% ≤ 38%, 30% ≤ (C1+C2) / U1 × 100% ≤ 40%, or 31% ≤ (C1+C2) / U1 × 100% ≤ 35%.
[0197] In some implementations, 0% ≤ C2 ≤ 16%; for example, 1% ≤ C2 ≤ 12%, 2% ≤ C2 ≤ 10%, 4% ≤ C2 ≤ 7%, or 5% ≤ C2 ≤ 9%.
[0198] In some embodiments, to improve the particle size uniformity of the first graphite, the particle size uniformity U2 of the artificial graphite obtained in step d) can satisfy 0.22 ≤ U2 ≤ 0.48. Optionally, 0.25 ≤ U2 ≤ 0.45, 0.26 ≤ U2 ≤ 0.43, 0.3 ≤ U2 ≤ 0.4, or 0.33 ≤ U2 ≤ 0.38.
[0199] In some embodiments, in step e), the organic carbon source may be selected from one or more of asphalt (e.g., coal tar pitch, petroleum asphalt), phenolic resin, coconut shell, etc.
[0200] In some embodiments, the heat treatment temperature in step e) can be 700°C to 1800°C, for example, 1000°C to 1300°C.
[0201] In some embodiments, in step e), the amount of organic carbon source C3 added during the coating process satisfies the following relationship with the volatile matter content C1 of the petroleum coke feedstock and the amount of binder C2 added during the granulation process: 10% ≤ C1+C2+C3 ≤ 25%; for example, 11% ≤ C1+C2+C3 ≤ 20%, 12% ≤ C1+C2+C3 ≤ 18%, or 13% ≤ C1+C2+C3 ≤ 16%. Satisfying this relationship between the amount of organic carbon source C3 added during the coating process and the volatile matter content C1 of the petroleum coke feedstock and the amount of binder C2 added during the granulation process can improve the proportion of secondary particles in the first graphite.
[0202] The amount of organic carbon source added during the coating process, C3, is the percentage of the weight of the organic carbon source added during the coating process relative to the total weight of the artificial graphite. In some embodiments, 2% ≤ C3 ≤ 8%, 2% ≤ C3 ≤ 5%, 3% ≤ C3 ≤ 5%, or 2% ≤ C3 ≤ 3%.
[0203] In some embodiments, in step e), the amount of organic carbon source C3 added during the coating process satisfies the following relationship with the volatile matter content C1 of the coke raw material, the amount of binder C2 added during the granulation process, and the particle size uniformity U2 of the artificial graphite: 20% ≤ (C1+C2+C3) / U2 × 100% ≤ 56%; for example, 30% ≤ (C1+C2+C3) / U2 × 100% ≤ 48%, 40% ≤ (C1+C2+C3) / U2 × 100% ≤ 48%.
[0204] In some implementations, in step e), the organic carbon source satisfies 1.2% ≤ C3 × char residue ≤ 2.5%; for example, 1.5% ≤ C3 × char residue ≤ 2.4%, 1.8% ≤ C3 × char residue ≤ 2.3%, or 2% ≤ C3 × char residue ≤ 2.2%.
[0205] When step e) still meets the above process conditions, the particle size consistency of the negative electrode active material, as well as the specific surface area and the proportion of secondary particles, can be further optimized, thereby further improving the performance of the battery.
[0206] The carbon residue rate is the carbon residue rate of organic carbon sources, which can be determined using the LP-5731 coal tar pitch coking value tester. The test can be performed in accordance with GB / T268 "Determination of Carbon Residue in Petroleum Products" and GB / T8727-2008 "Determination of Coking Value of Coal Tar Pitch Products".
[0207] Other anode active materials in the first anode active material can be obtained commercially or prepared by methods known in the art.
[0208] Besides the method for preparing the negative electrode sheet of this application, other structures and preparation methods of the secondary battery of this application are known. For example, the positive electrode sheet of this application can be prepared by the following method: the positive active material and optional conductive agent and binder are mixed and dispersed in a solvent (such as NMP), stirred evenly, coated on the positive current collector, dried, and cold-pressed to obtain the positive electrode sheet.
[0209] In some embodiments, a negative electrode, a positive electrode, a separator, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding or stacking process; the electrode assembly is placed in an outer package, an electrolyte is injected, and the secondary battery is obtained through processes such as vacuum sealing, settling, formation, and shaping.
[0210] The optional technical features of the secondary battery in this application are also applicable to the preparation method of this application.
[0211] Device A third aspect of this application provides an apparatus comprising at least one of the secondary battery, battery module, or battery pack described in this application. The secondary battery, battery module, or battery pack can be used as a power source for the apparatus or as an energy storage unit for the apparatus. The apparatus may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0212] The device can be configured to use a secondary battery, battery module, or battery pack, depending on its usage requirements.
[0213] Figure 10 This is an example device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0214] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.
[0215] Example The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0216] In the following embodiments and comparative examples, the artificial graphite A and natural graphite used in the second negative electrode active material, and the artificial graphite C and silicon suboxide SiO used in the first negative electrode active material, can all be commercially available or prepared by the following methods. The artificial graphite B (i.e., the first graphite) used in the first negative electrode active material can be prepared by the methods described herein.
[0217] (a) Preparation of artificial graphite A: Non-needle-shaped petroleum coke is used to obtain petroleum coke raw material by crushing; the petroleum coke raw material is shaped and graded to obtain a precursor; then the precursor is graphitized at 2800℃~3200℃ to obtain artificial graphite A.
[0218] In the above preparation method, optionally, the precursor can be granulated using binder pitch to adjust the particle morphology of artificial graphite A (for example, the proportion of primary particles in artificial graphite A can be adjusted).
[0219] In the above process, by adjusting the material preparation process, artificial graphite A is made to satisfy: 15 μm ≤ D v 50 ≤ 17.5 μm, 40 μm ≤ D v 99 ≤ 55 μm, with a specific capacity of 353 mAh / g ~ 370 mAh / g.
[0220] (II) Preparation of artificial graphite B: Petroleum coke is used to obtain petroleum coke raw material by crushing; the petroleum coke raw material is shaped and graded to obtain precursor; the precursor is granulated with binder asphalt, and then the granulated product is graphitized at 2800℃~3200℃ to obtain artificial graphite; after coating the artificial graphite with asphalt, it is carbonized and sieved to obtain artificial graphite B.
[0221] In the above process, the preparation process can be controlled according to the aforementioned preparation process of this application (see Table 2 for details) so that the artificial graphite B satisfies: 8μm ≤ D v 50 ≤ 13μm, D v99 ≤ 23μm, with a specific capacity of 348mAh / g ~ 360mAh / g.
[0222] (III) Preparation of artificial graphite C: Non-needle-shaped petroleum raw coke or petroleum calcined coke raw materials are used. The raw materials are crushed, shaped and graded to obtain precursors. The precursors are granulated with binder asphalt. The granulated products are then graphitized at a temperature of 2800℃~3200℃. After being coated with asphalt, artificial graphite is obtained by carbonization and sieving to obtain artificial graphite C.
[0223] In the above process, by controlling the material preparation process, artificial graphite C satisfies: 12 μm ≤ D v 50 ≤ 17 μm, 25 μm ≤ D v 99 ≤ 45 μm, with a specific capacity of 350 mAh / g ~ 360 mAh / g.
[0224] (iv) Natural graphite can be purchased from Shenzhen BTR New Energy Technology Co., Ltd., and the natural graphite meets the following requirement: 12μm ≤ D v 50 ≤ 19 μm, 24 μm ≤ D v 99 ≤ 37 μm, with a specific capacity of 360 mAh / g ~ 370 mAh / g.
[0225] (v) Silicon suboxide (SiO) is available from Shin-Etsu Chemical Co., Ltd.
[0226] Example 1 Preparation of negative electrode sheet The second negative electrode active material, artificial graphite A, conductive agent, carbon black (Super P), binder, styrene-butadiene rubber (SBR), and thickener, sodium carboxymethyl cellulose (CMC-Na), were thoroughly mixed in an appropriate amount of deionized water at a mass ratio of 96:1.5:1.5:1 to form a uniform second negative electrode slurry; wherein, the second negative electrode active material D... v 99 1 It is 45.2 μm.
[0227] The first negative electrode active material, artificial graphite B, conductive agent, carbon black (Super P), binder, styrene-butadiene rubber (SBR), and thickener, sodium carboxymethyl cellulose (CMC-Na), were thoroughly mixed in an appropriate amount of deionized water at a mass ratio of 96:1.5:1.5:1 to form a uniform first negative electrode slurry; wherein, the first negative electrode active material D... v 99 2 It is 22.9 μm.
[0228] The second negative electrode slurry and the first negative electrode slurry are simultaneously extruded using a dual-cavity coating device. The second negative electrode slurry is coated onto the copper foil of the negative electrode current collector to form a second negative electrode film, and the first negative electrode slurry is coated onto the second negative electrode film to form a first negative electrode film. After drying and cold pressing, the negative electrode sheet is obtained. The areal density of the negative electrode film is 0.123 mg / cm³. 2 The compacted density is 1.7 g / cm³. 3 The thickness ratio of the second negative electrode film to the first negative electrode film is 1:1.
[0229] Preparation of positive electrode sheet LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were mixed thoroughly in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The positive electrode slurry was then coated onto the surface of a positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained. The areal density of the positive electrode film was 0.188 mg / cm³. 2 The compacted density is 3.5 g / cm³. 3 .
[0230] Preparation of electrolyte Ethyl carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 4:3:3. LiPF6 was then uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 was 1 mol / L.
[0231] Separating membrane PE release film is used.
[0232] Preparation of secondary batteries The positive electrode, separator, and negative electrode are stacked and wound in sequence to obtain an electrode assembly. The electrode assembly is then placed in an outer package, and the electrolyte is added. After processes such as encapsulation, settling, formation, and aging, a secondary battery is obtained.
[0233] Examples 2-30 and Comparative Examples 1-6 The preparation method is similar to that in Example 1, except that the relevant parameters in the negative electrode preparation step are adjusted to obtain the corresponding secondary battery, as detailed in Tables 2 and 3.
[0234] Test section 1) Battery fast charging capability test At 25°C, the batteries of the above embodiments and comparative examples were charged and discharged for the first time at a current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour). Specifically, the batteries were charged at a constant current rate of 1C to a voltage of 4.25V, then charged at a constant voltage rate to a current ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a voltage of 2.8V. The actual capacity was recorded as C0.
[0235] Then, the battery is sequentially charged at constant current rates of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, and 3.0C0 until the full battery charging cutoff voltage of 4.25V or the negative terminal cutoff potential (whichever comes first). After each charge, it is discharged at 1C0 until the full battery discharge cutoff voltage of 2.8V. The charging rate is recorded at different rates until 10%, 20%, 30%, ..., 80% SOC (State of Charge). By plotting the negative electrode potential corresponding to the state of charge (SOC), the charging rate-negative electrode potential curves under different SOC states are obtained. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. This charging rate is the charging window under that SOC state, denoted as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC. The charging time T (assuming no lithium plating) from 10%SOC to 80%SOC is calculated according to the formula (60 / C20%SOC + 60 / C30%SOC + 60 / C40%SOC + 60 / C50%SOC + 60 / C60%SOC + 60 / C70%SOC + 60 / C80%SOC) × 10%, in minutes. The shorter the charging time, the better the battery's fast charging capability.
[0236] 2) Battery storage performance test At 25°C, the secondary batteries prepared in the examples and comparative examples were discharged at a constant current of 1.0C to 2.8V; then charged at a constant current of 1.0C to 4.25V, and continued to be charged at a constant voltage until the current ≤0.05C. At this point, the battery was in a fully charged state, i.e., 100% SOC. After the fully charged battery was left to stand for 5 minutes, it was discharged at a constant current of 1.0C to 2.8V. The discharge capacity at this point is the actual capacity of the battery at 1C / 1C, denoted as C0.
[0237] Then, at 25℃, the battery was charged at a constant current of 1C0 to 4.25V, and then charged at a constant voltage until the current ≤0.05C. At this point, the battery was fully charged. The fully charged battery was stored in an environment of 60℃. Following the established capacity testing procedure, the battery was periodically removed and discharged at 25℃ at a constant current of 1C0 to 2.8V, then charged at a constant current of 1C0 to 4.25V, and then charged at a constant voltage until the current ≤0.05C. After standing for 5 minutes, it was discharged at a constant current of 1.0C to 2.8V. The discharge capacity at this point is the reversible capacity after one storage cycle, denoted as C. n The capacity retention rate for this storage cycle is C. n / C0×100%. Repeat the storage test process until the capacity retention rate reaches 80%, then stop the test and record the storage time (days) at this point.
[0238] It should be noted that after each capacity test, the battery should be charged to 4.25V using 1C0, then charged at constant voltage until the current is ≤0.05C to bring the battery to a fully charged state, and then stored at 60℃.
[0239] 3) Battery cycle performance test At 25°C, the secondary batteries prepared in the examples and comparative examples were charged at a constant current of 0.33C to the charging cutoff voltage of 4.25V, then charged at a constant voltage to a current of 0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 0.33C to the discharge cutoff voltage of 2.8V. The initial capacity was recorded as C0. Then, charging and discharging at 0.33C were performed according to the strategy described in Table 1, and the discharge capacity C of each cycle was recorded. n Until the cycle capacity retention rate (C) n The percentage of the battery cycle life (C0×100%) is 80%, and the number of cycles is recorded. The more cycles, the higher the cycle life of the battery.
[0240] Table 1
[0241] The test results of Examples 1 to 30 and Comparative Examples 1 to 6 are detailed in Table 3.
[0242] Table 2: Preparation parameters of artificial graphite B
[0243] Table 3
[0244] Table 3 (continued)
[0245] As shown in Table 3, the secondary battery of this application embodiment employs a multi-layer negative electrode sheet, and the upper first negative electrode film layer contains a first negative electrode active material, satisfying that the first negative electrode active material includes a first graphite, and the D of the first negative electrode active material is... v With a thickness of 99 ≤ 23 μm, the battery can be charged at high rates even at high SOC, significantly improving its fast charging capability. Furthermore, the battery also achieves higher cycle performance and better storage capacity.
[0246] Batteries in Comparative Examples 1 to 6 do not meet the above conditions; they have poor fast charging capabilities, short cycle life, and are not conducive to improving storage performance.
[0247] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this application, and these modifications or substitutions should all be covered within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A secondary battery, comprising a negative electrode sheet (10), the negative electrode sheet (10) comprising a negative current collector (101) and a negative electrode film layer, the negative electrode film layer comprising a first negative electrode film layer (102) and a second negative electrode film layer (103), the second negative electrode film layer (103) being located between the negative current collector (101) and the first negative electrode film layer (102); The first negative electrode film layer (102) includes a first negative electrode active material; the first negative electrode active material includes a first graphite, which is artificial graphite, and the volume particle size distribution D of the first negative electrode active material is... v 99≤23 μm; The first graphite includes secondary particles, and the number of secondary particles in the first graphite accounts for ≥50%.
2. The secondary battery according to claim 1, wherein, The first negative electrode active material satisfies 17μm ≤ D v 99 ≤ 23 μm; optional, 18 μm ≤ D v 99 ≤ 21 μm.
3. The secondary battery according to any one of claims 1 to 2, wherein, The first negative electrode active material satisfies 8μm ≤D v 50 ≤ 13 μm; optional, 9 μm ≤ D v 50 ≤ 12 μm.
4. The secondary battery according to any one of claims 1 to 3, wherein, The particle size uniformity of the first negative electrode active material is 0.28 to 0.4, and optionally 0.30 to 0.
36.
5. The secondary battery according to any one of claims 1 to 4, wherein, The secondary particles account for 80% to 100% of the total amount in the first graphite.
6. The secondary battery according to any one of claims 1 to 5, wherein, The specific surface area of the first negative electrode active material is 0.45 m². 2 / g ~ 0.65m 2 / g, with an optional 0.5 m 2 / g ~ 0.63 m 2 / g.
7. The secondary battery according to any one of claims 1 to 6, wherein, The first negative electrode active material satisfies: 0.6 ≤ (D v 90-D v 10) / D v 50 ≤ 1.8; optional, 0.8 ≤ (D v 90-D v 10) / D v 50 ≤ 1.
4.
8. The secondary battery according to any one of claims 1 to 7, wherein, The volume particle size distribution D of the first negative electrode active material v 10 is 5μm ~ 9 μm, with an optional 6μm ~ 8 μm; or, The volume particle size distribution D of the first negative electrode active material v 90 has a thickness of 14μm to 21μm, with an optional thickness of 16μm to 18μm.
9. The secondary battery according to any one of claims 1 to 8, wherein, The first negative electrode active material also satisfies one or more of the following (1) to (5): (1) The powder OI value of the first negative electrode active material is 2.0 ~ 4.0, and optionally 2.3 ~ 3.6; (2) The tap density of the first negative electrode active material is 0.85 g / cm³. 3 ~ 1.4 g / cm 3 Optionally, it can be 0.9 g / cm³. 3 ~ 1.2 g / cm 3 ; (3) The compacted density of the first negative electrode active material under a pressure of 2 kN is 1.55 g / cm³. 3 ~ 1.70 g / cm 3 Optionally, it can be 1.58 g / cm³. 3 ~ 1.68 g / cm 3 ; (4) The specific surface area (SSA) of the first negative electrode active material is 0.8 m². 2 / g ~ 1.3 m 2 / g, with 0.9m being an optional value. 2 / g ~ 1.2 m 2 / g; (5) The specific capacity of the first negative electrode active material is 345 mAh / g ~ 360 mAh / g, and optionally 350 mAh / g ~ 358 mAh / g.
10. The secondary battery according to any one of claims 1 to 9, wherein, At least a portion of the surface of the first graphite has an amorphous carbon coating.
11. The secondary battery according to any one of claims 1 to 10, wherein, The first graphite accounts for ≥80% of the mass of the first negative electrode active material; optionally, the first graphite accounts for 90% to 100% of the mass of the first negative electrode active material.
12. The secondary battery according to any one of claims 1 to 11, wherein, The second negative electrode film layer (103) includes a second negative electrode active material, which includes a second graphite, which includes one or more of artificial graphite and natural graphite.
13. The secondary battery according to claim 12, wherein, The second graphite contains ≥50% artificial graphite by mass; optionally, the second graphite contains 60% to 100% artificial graphite by mass.
14. The secondary battery according to any one of claims 12-13, wherein, The volumetric particle size distribution D of the second negative electrode active material v 99 is greater than the volumetric particle size distribution D of the first negative electrode active material. v 99; Optionally, the volumetric particle size distribution D of the second negative electrode active material v 99 and the volume particle size distribution D of the first negative electrode active material v The ratio of 99 is 2.0 to 2.6, with an optional range of 2.1 to 2.
4.
15. The secondary battery according to any one of claims 12 to 14, wherein, The volume average particle size D of the second negative electrode active material v 50 has a thickness of 15μm to 21μm, and the optional thickness is 16.5μm to 20μm.
16. The secondary battery according to any one of claims 12 to 15, wherein, The particle size uniformity of the second negative electrode active material is 0.3 to 0.55, and optionally 0.4 to 0.
5.
17. The secondary battery according to any one of claims 12 to 16, wherein, The second graphite includes primary particles; optionally, the primary particles account for ≥50% of the number of the second graphite; optionally, the primary particles account for 60% to 100% of the number of the second graphite.
18. The secondary battery according to any one of claims 12 to 17, wherein, The particle size specific surface area of the second negative electrode active material is 0.35 m². 2 / g ~ 0.55m 2 / g, with an optional value of 0.38 m 2 / g ~ 0.50 m 2 / g.
19. The secondary battery according to any one of claims 12 to 18, wherein, The second negative electrode active material also satisfies one or more of the following conditions (1) to (8): (1) The second negative electrode active material satisfies: 0.9 ≤ (D v 90-D v 10) / D v 50 ≤ 1.6; optional, 1.0 ≤ (D v 90-D v 10) / D v 50 ≤ 1.4; (2) The volume particle size distribution D of the second negative electrode active material v 10 has a thickness of 5μm to 14μm, with optional thicknesses of 7μm to 12μm; (3) The volume particle size distribution D of the second negative electrode active material v 90 has a thickness of 24μm to 38μm, with an optional thickness of 26μm to 33μm; (4) The OI value of the powder of the second negative electrode active material is ≤14, and can be 6 ~ 11; (5) The tap density of the second negative electrode active material is 0.8 g / cm³. 3 ~ 1.2 g / cm 3 Optionally, it can be 0.9 g / cm³. 3 ~ 1.1 g / cm 3 ; (6) The compacted density of the second negative electrode active material under a pressure of 2 kN is 1.70 g / cm³. 3 ~ 1.85 g / cm 3 Optionally, it can be 1.75 g / cm³. 3 ~ 1.82 g / cm 3 ; (7) The specific surface area (SSA) of the second negative electrode active material is 1.0 m². 2 / g ~ 2.0 m 2 / g, with an optional 1.3m 2 / g ~ 1.8 m 2 / g; (8) The specific capacity of the second negative electrode active material is 353 mAh / g ~ 370 mAh / g, and optionally 359 mAh / g ~ 367 mAh / g.
20. The secondary battery according to any one of claims 1 to 19, wherein, The negative electrode film layer also satisfies one or more of the following (1) to (3): (1) The areal density of the negative electrode film is 0.117 mg / mm². 2 ~ 0.130 mg / mm 2 The optional value is 0.120 mg / mm. 2 ~ 0.127 mg / mm 2 ; (2) The compaction density of the negative electrode film is 1.65 g / cm³. 3 ~ 1.75 g / cm 3 The optional value is 1.66 g / cm³. 3 ~1.70 g / cm 3 ; (3) The thickness ratio of the second negative electrode film layer (103) to the first negative electrode film layer (102) is 0.7:1 ~ 2.3:1, optionally 0.7:1 ~ 1.0:1, and even more optionally 1.1:1 ~ 2.3:
1.
21. The secondary battery according to any one of claims 12 to 20, wherein, The first or second negative electrode active material further includes one or more of silicon-based materials, tin-based materials, soft carbon, hard carbon, and lithium titanate.
22. The secondary battery according to any one of claims 1 to 21, wherein, The secondary battery includes a positive electrode sheet, which includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector and including a positive electrode active material. The positive electrode active material includes one or more of lithium transition metal oxides, lithium phosphates with olivine structures, and their respective modified compounds. Optionally, the positive electrode active material includes one or more of the lithium transition metal oxides and their modified compounds represented by Formula 1. Li a Ni b Co c M d O e A f Formula 1, In Formula 1, 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from one or more of N, F, S and Cl.
23. A method for preparing a secondary battery, comprising at least the following steps: A second negative electrode film layer is formed on at least one side of the negative electrode current collector, the second negative electrode film layer comprising a second negative electrode active material; A first negative electrode film layer is formed on the surface of the second negative electrode film layer, and the first negative electrode film layer includes a first negative electrode active material. in, The first negative electrode active material includes a first graphite, which is artificial graphite, and the volume particle size distribution D of the first negative electrode active material is... v 99 ≤ 23 μm.
24. A battery module comprising a secondary battery according to any one of claims 1 to 22, or a secondary battery prepared by the method according to claim 23.
25. A battery pack comprising a secondary battery according to any one of claims 1 to 22, a secondary battery prepared by the method according to claim 23, or a battery module according to claim 24.
26. An apparatus comprising at least one of the following: a secondary battery according to any one of claims 1 to 22, a secondary battery prepared by the method according to claim 23, a battery module according to claim 24, or a battery pack according to claim 25.
